Stable and bright commercial CsPbBr₃ quantum dot-resin layers for apparent X-ray imaging screen - Maddalena, Francesco (2022)
CsPbBr3 quantum dots (QDs) have recently gained much interest due to their excellent optical and scintillation properties and their potential for X-ray imaging applications. In this study, we blended CsPbBr3 QDs with resin at different QD concentrations to achieve thick films and to protect the CsPbBr3 QDs from environmental moisture. Then, their scintillation properties are investigated and compared to the traditional commercial scintillators, CsI:Tl microcolumns, and Gadox layers. The CsPbBr3 QD-resin sheets show a high light yield of up to 21 500 photons/MeV at room temperature and a relatively small variation in light yield across a wide temperature range. In addition, the CsPbBr3 QD-resin sheets feature a small scintillation afterglow. The CsPbBr3 QD-resin sheets show a negligible trap density for the concentration below 50% weight, indicating that traps might arise from the aggregation of the QDs. The CsPbBr3 QD-resin sheets are also very stable at low irradiation intensities and relatively stable at higher intensities, with higher CsPbBr3 QD concentrations being more stable. Gamma-ray-excited-time-resolved emission measurements at 662 keV showed that the CsPbBr3 QD-resin sheets have an average scintillation decay time between 108 and 176 ns, which are still 10 000 and 6000 times faster than CsI:Tl and Gadox, respectively. Imaging tests show that the CsPbBr3 QD-resin sheets have a mean transfer function of 50% at 2 lp/mm and 20% at 4 lp/mm, comparable to that of commercial Gadox layers. This feature makes CsPbBr3 QD-resin sheets a good candidate for the low-cost, flexible X-ray imaging screens and γ-ray applications.